Standard Life: encouraging older consumers to invest in health insurance - Kiddle, Janet (Henry Stewart Talks, 2016)
The case study reviews research conducted on behalf of Standard Life, an insurance company based in the UK that was planning to launch a health insurance scheme for the over 55 age group. It examines the market research undertaken to inform the scheme and in particular the best ways of marketing it to older consumers.